Bycatch of common pollinators in pheromone baited traps for monitoring corn earworm (Lepidoptera: Noctuidae) in Missouri Industrial Hemp - Clement Akotsen-Mensah; Isaac N. Ativor; Caroline N. Foba; Valliyodan Babu (Journal of Cannabis Research)
Abstract Background Several traps are recommended for monitoring corn earworm, Helicoverpa zea (Boddie), an important pest of field, vegetable and fruit crops in the U.S. These traps, which are meant to capture H. zea in many cases end up capturing other insects. Helicoverpa zea has recently been found feeding on different seeds and dual-type (seed and fiber) hemp, Cannabis sativa L. (Rosales: Cannabaceae) causing serious damage. Limited work has been done on developing integrated pest management (IPM) for H. zea industrial hemp in Missouri. Methods We evaluated the attractiveness of different traps with the aim of developing a monitoring system for the adult male H. zea in industrial hemp fields in two Missouri locations. In addition, we recorded other non-target insects in the traps to determine trap selectivity. Commercially available green, clear, tricolor bucket traps Heliothis Scentry and Scentry Delta 1X traps baited with H. zea sex pheromones were evaluated in 2021 and 2022. Results Tricolor traps captured significantly more adult male H. zea than the other traps in both years. Non-target insects, mainly Xylocopa virginica (L.) (Hymenoptera: Apidae), Bombus spp. (Hymenoptera: Apidae), and Apis mellifera L. (Hymenoptera: Apidae) were also captured. The tricolor trap captured the most bees. Conclusions The presence of non-target species highlights the risk of using tricolor traps as a monitoring tool. This data provides information for planning the monitoring of corn earworm in industrial hemp farms in Missouri.